The Role of Educational Process in the Formation of a Harmoniously Developed Generation and Methods of using Modern Teaching Technologies - Narzullaevna, Kurbanova Shoira (Research Parks Publishing LLC, 2022)
The article reveals effective ways to use innovative technologies in the formation of a harmoniously developed generation. There is talk of game technology and methods that can be used to teach.